Has Co-Movement Dynamics In Brazil, Russia, India, China And South Africa (BRICS) Markets Changed after Global Financial Crisis? New Evidence from Wavelet Analysis - M. Kannadhasan; Debojyoti Das (Asian Academy of Management Journal of Accounting and Finance, 2019)
We investigate the changes in the co-movement dynamics in the stock market returns of Brazil, Russia, India, China and South Africa (BRICS) with that of US during pre and post-global financial crisis (GFC). The stock returns of BRICS and the US markets over the period of 1999–2016 are analysed using wavelet transformation, with equal time phase of eight years on both sides of GFC. We find the existence of co-movement at both high and low frequencies. In addition, the contagion effect is also noted around the GFC year 2008. Further we also report that despite the high correlation of BRICS portfolio, it facilitates asset diversification benefits in the medium run. Finally, there is significant changes in correlation dynamics for Russia and China during post-GFC period, whereas the multiple correlations dynamics amongst BRICS markets remain unchanged.